Optimizing Sustainable Concrete Strength With Laminated Waste Glass (Lwg): Insights From Waterto-Cement Ratios And Slump Values (0.35-0.5) - Mohd Roslan, Muhammad Lutfi Fitri; Mohd Zuki, Sharifah Salwa; Shahidan, Shahiron; Mohammad Azmi, Mohamad Azim (2024)
This study investigates the use of laminated waste glass (LWG) as a fine aggregate in concrete, with a focus on optimizing strength and workability through variation in water-to-cement (w/c) ratios. A series of experiments were conducted to assess the compressive strength, split tensile strength, and slump attributes of LWG concrete with w/c ratios ranging from 0.35 to 0.5 and a 15% replacement of fine aggregate with LWG. Results showed that a w/c ratio of 0.42 offered optimal conditions for achieving M30 grade LWG concrete, with impressive compressive and tensile strengths of approximately 64.5 MPa and 3.2 MPa, respectively, for the LWG concrete formulation with a w/c ratio of 0.35. The study highlights the potential of LWG as a sustainable alternative to natural aggregates in concrete, with the added benefit of reducing waste. The findings have practical implications for sustainable construction practices, offering insights into the use of LWG in concrete mix design to achieve desired strength and workability.